A review of exenatide as adjunctive therapy in patients with type 2 diabetes - Gisela I Robles; Devada Singh-Franco (Dove Medical Press, 2009)
Gisela I Robles, Devada Singh-FrancoNova Southeastern University, College of Pharmacy, Health Professions Division, Fort Lauderdale, FL, USABackground: Incretin glucagon-like peptide-1 (GLP-1) is a hormone released from cells in the gastrointestinal tract (GI), leading to glucose-dependent insulin release from the pancreas. It also suppresses postprandial hyperglycemia, glucagon secretion and slows gastric emptying. Exenatide (EXE), a functional analog of human GLP-1, was approved by the US FDA in April 2005.Objective: This article reviews current primary literature on the clinical efficacy and safety of EXE in the treatment of type 2 diabetes mellitus (DM) and describes the pharmacokinetics, pharmacodynamics, dosing and administration of EXE.Methods: English-language articles were identified through a search of MEDLINE (1966 to March 2009), International Pharmaceutical Abstracts (1970 to present), and Cochrane Database of Systemic Reviews (1995 to March 2009). Search terms included EXE, diabetes mellitus, postprandial hyperglycemia, gastric emptying, glucagon, pharmacokinetics and pharmacodynamics. Articles were selected for review if their designs were randomized, blinded and of controlled design that focused on clinical outcomes of patients with type 2 DM.Results: EXE is administered subcutaneously in the thigh, abdomen or upper arm within the 60-minute period before the morning and evening meals. Its Cmax is reached within 2.1 hours, and its T1/2 in 2.4 hours. EXE’s metabolism is primarily through the kidneys. For the patients who received EXE 10 µg SC BID in three, 30-week, placebo-controlled studies with background sulfonylureas (SUs), metformin (MET), or SU + MET, there were significant reductions in HbA1c (0.77 to 0.86%), fasting plasma glucose (0.6 mmol/L) and body weight (1.6 to 2.8 kg) (P ≤ 0.05 vs PCB) that were sustained in patients who completed two open-label phase trials with an additional 52 weeks of therapy. The use of thiazolidinediones was associated with a slight advantage over EXE in improving HbA1c along with increased weight gain; those who received EXE lost weight, but experienced more GI adverse effects. Patients who received EXE lost significant body weight while patients who received insulin gained weight. Patients receiving insulin had lower fasting, prelunch and predinner glucose excursions while patients in the EXE groups had lower postprandial glucose levels. Nausea was most frequently (>20%) reported in patients receiving the highest dose of EXE (10 µg SC BID vs 5 µg SC BID).Conclusions: EXE at the dose of 10 µg SC BID has been proven to decrease HbAlc by 1.3% ± 0.1% and decrease body weight by up to 5.3 ± 0.8 kg at week 82. Nausea was the most frequently reported adverse event (>20%) especially in patients being treated with EXE 10 µg SC BID. EXE can be safely added to MET therapy, SU therapy or MET + SU combination to effectively target glycemic goals in patients with type 2 DM. Long-term, head-to-head studies assessing the effect of the EXE ± oral agents/insulins in patients with HbAlc ≥ 10% are still needed to fully clarify the role of EXE in poorly controlled patients with type 2 DM.Keywords: exenatide, glucagon-like peptide-1, incretin, pharmacokinetics, pharmacodynamics, pharmacoeconomic, postprandial hyperglycemia, gastric emptying, glucagon